2014
DOI: 10.5812/aapm.19384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SubhypnoticDosesof Propofol and Midazolam for Nausea and Vomiting DuringSpinal Anesthesia for Caesarean Section

Abstract: Background:Spinal anesthesia has been associated with intraoperative nausea and vomiting (IONV), especially during cesarean section, which is attributed to several mechanisms.Objectives:In the present study, therapeutic and preventive properties of sub hypnotic dose midazolam and propofol and their effects on the occurrence and severity of intraoperative nausea and vomiting during elective cesarean section under spinal anesthesia were evaluated.Patients and Methods:In a randomized, double-blind, and placebo-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
3
28
1
Order By: Relevance
“…35 In contrast, Rasooli et al found that subhypnotic doses of both agents effectively prevent peri-and postoperative nausea and vomiting in patients underwent C/S after SA. 36 Likewise, we found lower nausea and vomiting incidences in parturients during C/S, but this time by using IV thiopental.…”
Section: Discussionmentioning
confidence: 65%
“…35 In contrast, Rasooli et al found that subhypnotic doses of both agents effectively prevent peri-and postoperative nausea and vomiting in patients underwent C/S after SA. 36 Likewise, we found lower nausea and vomiting incidences in parturients during C/S, but this time by using IV thiopental.…”
Section: Discussionmentioning
confidence: 65%
“…Hypotension observation rates and associated nausea and vomiting are common in cesarean section performed under spinal anesthesia (4,19). In a study conducted by Voigt et al (20), the incidence of hypotension in cesarean was identified as 46.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-operative nausea and vomiting rate was observed as 46.15% in the same study. The most commonly used method for the treatment of nausea and vomiting observed due to hypotension formed by the effects of spinal anesthesia is the use of vasopressor medications, especially the use of ephedrine in order to prevent hypotension (7,19). Considering the side effects of ephedrine used for the treatment of hypotension that occurs after spinal anesthesia in caesarean operations performed under spinal anesthesia, studies have been conducted to identify different doses of ephedrine or new drugs and techniques that can be used instead of ephedrine (4,5,16,21).…”
Section: Discussionmentioning
confidence: 99%
“…Its hypnotic effect is also positively correlated with dose, so an increased dose may increase the risk of obstruction in the upper respiratory tract due to glossocoma. Since the specific condition of pregnant woman may more easily result in respiratory complications such as glossoco- 154 ma, a dose of less than 0.05 mg/kg is recommended for pregnant women [27] . In this study, the doses of midazolam were relatively low in both the groups, the changes in RR and SpO2 were not marked.…”
Section: Discussionmentioning
confidence: 99%